2011
DOI: 10.1021/ol202069e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Hindered Morita–Baylis–Hillman Adducts by Rh(I)-Catalyzed Asymmetric 1,4-Addition/β-Hydroxyelimination

Abstract: A kinetic resolution of hindered Morita-Baylis-Hillman adducts has been successfully achieved in excellent selectivities via Rh(I)-catalyzed asymmetric 1,4-addition/β-hydroxyelimination with the use of a chiral sulfinamide/olefin hybrid ligand. This study provides a novel and efficient access to both optically active hindered highly functionalized alkenes and Morita-Baylis-Hillman adducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 71 publications
(15 reference statements)
0
14
0
Order By: Relevance
“…Kinetic resolution can be employed to obtain optically pure or enriched molecules therefrom. [20][21][22] The use of enzymes for the kinetic resolution of secondary carbinols is well documented, 23,24 and has proved to be economically and environmentally advantageous. Previous studies regarding biocatalytic resolution of enantiomers of 3(RS)-hydroxy-2-methylenebutanenitrile 1(RS) were focused on the optimization of transesterification reaction conditions using lipase from Pseudomonas cepacia.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic resolution can be employed to obtain optically pure or enriched molecules therefrom. [20][21][22] The use of enzymes for the kinetic resolution of secondary carbinols is well documented, 23,24 and has proved to be economically and environmentally advantageous. Previous studies regarding biocatalytic resolution of enantiomers of 3(RS)-hydroxy-2-methylenebutanenitrile 1(RS) were focused on the optimization of transesterification reaction conditions using lipase from Pseudomonas cepacia.…”
Section: Introductionmentioning
confidence: 99%
“…In the reactions using acrylamides and enamides, the coordination of the amide carbonyl into rhodium induce high reactivity and selectivity,a nd suppresst he undesired b-hydrogen elimination giving dienep roducts. [6, 7a, 9] In 2016, Roglans andP la-Quintana reported that racemic secondary allylic alcohols [10] react with 1,6-diynes through the kinetic resolution [11] in the presenceo facationic rhodium(I)/ binap complex to give bicyclic cyclohexadienes (Scheme 1b). [12] This reactionc an construct contiguous two stereogenic centers as as ingled iastereomer with high ee values, whilet he substrate scope was somewhat limited( methoxycarbonyl-and aryl-substituted allylic alcohols, ands ulfonamide-linked and dimethyl-substituted 1,6-diynes).Inthis Communication, we have established that ac ationic rhodium(I)/Pphos complex is capableo fc atalyzing the regio-,d iastereo-, and enantioselective [2+ +2+ +2] cycloaddition of 1,6-enynes with racemic secondary allylic alcohols through the kineticr esolution at room temperature giving chiralb icyclic cyclohexenes, possessing three stereogenic centers (Scheme 1c).…”
mentioning
confidence: 99%
“…[13,14] These studies demonstrated that simple and readily available chiral sulfur-olefin hybrid ligands can also display great catalytic activities and enantioselectivities in asymmetric catalysis. We have recently become intrigued by the possibility of their application in the more challenging enantioselective 1,2-addition of aryl boronic acids to more activated ketones, such as a-ketoesters and a-diketones, to provide optically active, functionalized tertiary alcohols.…”
mentioning
confidence: 99%
“…The catalytic asymmetric addition to a-diketones represents an unprecedented synthesis of optically active, tertiary a-hydroxyketone derivatives. Moreover, aside from their use in 1,4-addition to a,b-unsaturated carbonyl compounds, [13,14] this is the first example of the successful application of the recently developed, chiral sulfur-olefin ligands in asymmetric catalysis, wherein the unique sulfonamide-olefin 3 has been shown to be highly effective. It opens new opportunities for the use of this novel class of readily available ligands in related asymmetric processes.…”
mentioning
confidence: 99%